2021
DOI: 10.1016/j.tranon.2020.100916
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-targeting anti-EGFR x anti-PD1 bispecific antibody inhibits EGFR-overexpressing tumor growth by combining EGFR blockade and immune activation with direct tumor cell killing

Abstract: Highlights The anti-PD1 x anti-EGFR bispecific antibody (BsAb) exhibited all in-vitro bioactivities comparable to that of the parental mAbs and showed anti-tumor efficacies of each of the two arms on par with the mAbs in-vivo. The anti-PD1 x anti-EGFR bispecific antibody (BsAb) retained full ADCC towards cancer cells but not to T cells. Thus the BsAb is capable of killing tumor cells via ADCC while sparing T cells for T cell-induced anti-tumor immunity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…4b ). This result is in line with the previous finding where a BsAb with anti-PD1 scFvs fused to the N-terminus of cetuximab showed no ADCC toward T cells [ 39 ]. This suggests that proper spacing between the cell surface receptors and the Fc region of an IgG molecule or a favorable protein configuration as a whole, such as an intact IgG format, might be a critical determinant for initiating ADCC.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…4b ). This result is in line with the previous finding where a BsAb with anti-PD1 scFvs fused to the N-terminus of cetuximab showed no ADCC toward T cells [ 39 ]. This suggests that proper spacing between the cell surface receptors and the Fc region of an IgG molecule or a favorable protein configuration as a whole, such as an intact IgG format, might be a critical determinant for initiating ADCC.…”
Section: Resultssupporting
confidence: 93%
“…Given that the BsAb can crosslink PD1 on T cells and HER2 on tumor cells, we hypothesized that the BsAb may enhance tumor cell killing by bringing T cells into the proximity of tumor cells and potentially inducing PD1 synapse formation as seen in our previous study [ 39 ]. We stably transfected NCI-N87 cells, a HER2-overexpressing gastric cancer cell line that does not express PDL1 when cultured in vitro (data not shown), with a PDL1 construct to obtain a PDL1/HER2 double-overexpressing cancer cell line (N87-PDL1) that could potentially respond to trastuzumab and anti-PD1 mAbs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…149 Moreover, checkpoint blockades have been incorporated into BsAbs to achieve tumorlocalized and TAA-dependent checkpoint blockage. 150,151 For example, an anti-PD-1 × HER2 (human epidermal growth factor receptor 2) BsAb (IBI315, Innovent, Inc., China) was designed to bridge PD-1-expressing T cells to HER2-expressing tumor cells, block the PD-1/PD-L1 signaling pathway in a HER2-dependent manner, and inhibit activation of the HER2 signaling pathway. 152 As a result, IBI315 combines targeted therapy with immunotherapy, thereby potentially enhancing antitumor activity via multiple mechanisms of action.…”
Section: Targeting Checkpoint Receptors On T Cellsmentioning
confidence: 99%
“…Similarly, an anti-PD-1 × EGFR IgG scaffold-based BsAb has exhibited potent antitumor efficacy and enhanced T cell-based antitumor immunity through PD-L1 blockade in both in vitro and in vivo models. 151 Simultaneous blockade of two immune checkpoints with synergic mechanisms of action has been used to maximize checkpoint blockade in the TME. 153 , 154 A clinical trial showed that five-year outcomes of applying nivolumab (anti-PD-1) plus ipilimumab (anti-CTLA-4) to treat patients with advanced melanoma led to sustained long-term OS compared with treatment with ipilimumab alone, 155 providing a rationale for concurrently targeting two immune checkpoints.…”
Section: Multispecific Antibodiesmentioning
confidence: 99%